2010
DOI: 10.5142/jgr.2010.34.2.138
|View full text |Cite
|
Sign up to set email alerts
|

Anti-apoptotic Effects of Red Ginseng on Oxidative Stress Induced by Hydrogen Peroxide in SK-N-SH Cells

Abstract: Ginseng (Panax ginseng C.A. Meyer) has been shown to have anti-stress effects in animal studies. However, most studies have only managed to detect altered levels of biomarkers or enzymes in blood or tissue, and the actual molecular mechanisms by which ginseng exerts these effects remain unknown. In this study, the anti-oxidative effect of Korean red ginseng (KRG) was examined in human SK-N-SH neuroblastoma cells. Incubation of SK-N-SH cells with the oxidative stressor hydrogen peroxide resulted in significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 28 publications
(25 reference statements)
1
13
0
Order By: Relevance
“…RG extract decreased the expression of pro-apoptotic protein, caspase-3 and increased that of anti-apoptotic protein, bcl-2 to protect the human neuroblastoma, SK-N-SH cells against hydrogen peroxide-induced oxidative stress [30]. Also, water extract of American ginseng root has been investigated to prevent apoptosis by increasing the protein level of bcl-2 and decreasing that of caspase-9 in β cells cultured with interleukin-1β [7].…”
Section: Resultsmentioning
confidence: 99%
“…RG extract decreased the expression of pro-apoptotic protein, caspase-3 and increased that of anti-apoptotic protein, bcl-2 to protect the human neuroblastoma, SK-N-SH cells against hydrogen peroxide-induced oxidative stress [30]. Also, water extract of American ginseng root has been investigated to prevent apoptosis by increasing the protein level of bcl-2 and decreasing that of caspase-9 in β cells cultured with interleukin-1β [7].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, ginsenoside Rg1 functions as an agonist at the glucocorticoid receptor, leading to the production of NO by eNOS via the non-transcriptional PI3K/Akt pathway [28]. KRG also inhibits hydrogen peroxide-induced cell death by decreasing the expression of the pro-apoptotic protein caspase-3 and the pro-inflammatory protein cyclooxygenase 2, and increasing the expression of the anti-apoptotic protein Bcl-2 [2]. Consistent with this, KRG increased the NO concentration in the exhaled breath of healthy human subjects [15].…”
Section: Discussionmentioning
confidence: 99%
“…PWV is also affected by endothelial function and is regulated by endothelium-derived NO and hyperpolarizing factor [25,26]. KRG has probable anti-oxidative properties; it is known to promote NO production and to protect endothelial cells from oxidative stress [2,15,27,28]. The ginsenoside PPT protects endothelial cells from hydrogen peroxide-induced cell injury and death by ameliorating oxidative stress [27].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, 38 ginsenosides have been found to bear the potential of exerting distinct effects on the endothelial cells, prevention of programmed cell death, regulation of angiogenesis, and stabilizing blood pressure. Intriguingly, it is reported that ginsenosides can enhance endothelial function [29,47]. Additionally it is also reported that P. ginseng can induce the activity of the enzymes of the CYP450 family and as a consequence lower the bioavailability of a number of drugs including warfarin [26].…”
Section: Ginkgo Biloba L (Ginkgoaceae) -Ginkgomentioning
confidence: 99%